DISPARITAS PUTUSAN HAKIM DALAM PERKARA KECELAKAAN LALU LINTAS YANG MENGAKIBATKAN HILANGNYA NYAWA ORANG LAIN (STUDI PUTUSAN NOMOR: 424/PID.SUS/2018/PN.AMB DAN PUTUSAN NOMOR: 494/PID.SUS/2018/PN.AMB) - Adithia warman; R Rahaditya (Jurnal Hukum Adigama, 2020)
Disparity of sentencing in law enforcement be perceived often occurs, as an example existence disparity of sentencing on criminal act in the traffic field and road transport between Court Decision Number: 424/Pid.Sus/2018/PN Amb and Court Decision Number: 494/Pid.Sus/2018/PN Amb. The issue of disparity of sentencing appears because regulation of criminal law in Indonesia is still not optimal. Other than that, factors that come from the judges themselves can trigger the emergence of this disparity of sentencing. Referring to the problem, the writer conducted research by using normative methods and also supported interview data from some interviewees. The research result shows that the law in effect in Indonesia at this time still needs some renewal in order to minimize disparity of sentencing, as an example be required to regulate the purpose of sentencing, the guidance of sentencing, or regarding the existence of a special minimum of sentencing. Other than that, the integrity of judges must also get attention. Judges are required to always obey existing laws and regulations, and pay attention to the values that live in society, in order to uphold legal justice and also legal certainty and legal benefit.